2020
DOI: 10.1177/1046878120916209
|View full text |Cite
|
Sign up to set email alerts
|

Optimising the Learning Potential of Simulations Through Structural Transparency and Exploratory Guidance

Abstract: Background. Simulation-based learning environments are used extensively to support learning in complex business systems. Nevertheless, studies have identified problems and limitations due to cognitive processing difficulties. In particular, previous research has addressed some aspects of model transparency and instructional strategy and produced inconclusive results. Aim. This study investigates the learning effects of using transparent simulations (that is, showing users the internal structure of models) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 57 publications
2
7
0
Order By: Relevance
“…Nevertheless, however, courses of action of students submitted to that condition did not show that they consistently improved their comprehension of the model dynamics. This result is consistent with the findings reported by Capelo and Silva (2020) that subjects submitted to transparent conditions are able to acknowledge certain cause-and-effect relations, but they fail to mentally infer the model behaviour. This conclusion is in line with a learning difficulty frequently mentioned in system dynamics literature (Davidsen & Spector, 2015): that it is difficult to develop an understanding of how the behaviour of a complex system emerges from its underlying causal structure.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nevertheless, however, courses of action of students submitted to that condition did not show that they consistently improved their comprehension of the model dynamics. This result is consistent with the findings reported by Capelo and Silva (2020) that subjects submitted to transparent conditions are able to acknowledge certain cause-and-effect relations, but they fail to mentally infer the model behaviour. This conclusion is in line with a learning difficulty frequently mentioned in system dynamics literature (Davidsen & Spector, 2015): that it is difficult to develop an understanding of how the behaviour of a complex system emerges from its underlying causal structure.…”
Section: Discussionsupporting
confidence: 92%
“…Kopainsky and Alessi (2015) found that participants provided with the more transparent strategy demonstrated better understanding of the underlying model, but their performance, however, was equivalent to those in the less transparent situation. More recently, Capelo and Silva (2020) analysed the learning effects of using transparent simulations (that is, showing participants the model SFD) and exploratory guidance (that is, guiding learners so they are able to explore the simulation by themselves) and found that while the transparent strategy combined with the exploratory guidance is a beneficial method for understanding both model structure and behaviour, making the model transparent alone is more limited in its effect. The implication of the previous studies is that students must not only identify the structure of the simulator model but also have to recognise the relationship between structure and behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have evidenced the positive learning effects of using simulations in various domains of management and business education. For instance, Capelo et al (2015) and Burdon and Munro (2017) investigated the use of simulations on accounting courses; Huang and Hsu (2011) explored the use of online games to teach personal finance concepts; Pasin and Giroux (2011) analysed the effects of simulation on operations management education; Capelo and Silva (2020) and Sarkar (2016) used simulations on supply chain management courses; Nisula & Pekkola (2012) and Hwang & Cruthirds (2017) focused on ERP learning; Vos and Brennan (2010) applied simulation games in marketing classes; Loon, Evans, and Kerridge (2015) investigated the use of strategic management simulations. Bianchi and Bivona (2000) used interactive learning environments linking SD and accounting models as a teaching aid in the education of small business entrepreneurs.…”
Section: Sbles In Business and Management Educationmentioning
confidence: 99%
“…However, whilst the benefits of SBLEs are often discussed in the literature, there is still a need for more research addressing how the learning potential of such environments might be enhanced (Davidsen & Spector, 2015). According to the literature, the effectiveness of SBLEs depends on many factors, e.g., a critical thinking disposition (Bell & Loon, 2015), intrinsic motivation and engagement (Buil, Catalán, & Martínez, 2019), the method of instruction (Capelo & Silva, 2020), and type of facilitation (Qudrat-Ullah, 2014;Hughes & Scholtz, 2015).…”
Section: Sbles In Business and Management Educationmentioning
confidence: 99%
“…Capelo and Silva (2020) also conducted an empirical simulation experiment with business students, adding further to this vital focus on the design and application of simulation games. Based on a system dynamics model and supply chain business game they research and discuss the effects of structural transparency and exploratory guidance for optimizing the learning potential of simulation games.…”
Section: The Articles Of the August 2020 Issuementioning
confidence: 99%